Efek Penyebaran Korean Wave (Hallyu) di Indonesia Terhadap Perilaku Konsumtif Penggemarnya Perspektif Islam - Safitri, Nur; Putri Anjeli, Shakira; Sazali, Hasan; Andinata, Maulana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Globalization makes foreign popular culture contact Indonesia. Such cultural assimilation is consciously or unconsciously accepted and spread in society. Hallyu is a word that refers to the international spread of Korean popular culture in various countries around the world. The Korean Wave is the spread of Korean popular culture through entertainment products such as K-drama and K-POP. This causes the congregation to engage in excessive consumerism, which is discouraged in Islam. KPOP culture is often associated with consumption, as money is regularly spent on KPOP merchandise over a period of time. which method used is qualitative and descriptive, aims to study consumption behavior K-Pop and K-Drama fans related to the Korean Wave phenomenon. The survey results show that the majority of respondents agree that the behavior of people who frequently buy their idol's products is included in consumer behavior.